RING finger protein 5 is a key anti-FMDV host factor through inhibition of virion assembly. - Wei Zhang; Weiwei Li; Yang Yang; Weijun Cao; Wenhua Shao; Mengyao Huang; Jiali Wang; Zhitong Chen; Jiantao Cai; Hongyi Liu; Xiaoyi Zhao; Xingyan Dong; et al. (PLoS Pathogens)
Foot-and-mouth disease virus (FMDV) are small, icosahedral viruses that cause serious clinical symptoms in livestock. The FMDV VP1 protein is a key structural component, facilitating virus entry. Here, we find that the E3 ligase RNF5 interacts with VP1 and targets it for degradation through ubiquitination at the lys200 of VP1, ultimately inhibiting virus replication. Mutations at this lysine site have been found to increase the replication of FMDV in mice. Importantly, the RNF5 pharmacological activator Analog-1 alleviates disease development in a mouse infection model. Furthermore, RNF5 recognizes the VP1 protein from several picornaviruses, suggesting that targeting RNF5 may be a broad-spectrum antiviral strategy. These findings shed light on the role of the ubiquitin-proteasome system in controlling virus replication, offering potential new strategies for treating viral infections.